2017
DOI: 10.1111/cen.13350
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in athletic performance emerge coinciding with the onset of male puberty

Abstract: The gender divergence in athletic performance begins at the age of 12-13 years and reaches adult plateau in the late teenage years with the timing and tempo closely parallel to the rise in circulating testosterone in boys during puberty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(138 citation statements)
references
References 26 publications
8
127
2
1
Order By: Relevance
“…The divergence in athletic performance between men and women at puberty when serum testosterone levels diverge, has been well demonstrated, 45 and is a natural and well recognized progression to adulthood. Also, recent studies of androgen levels in elite athletes have suggested that female athletes with high testosterone levels, free or total, may have a significant competitive advantage over those with low testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…The divergence in athletic performance between men and women at puberty when serum testosterone levels diverge, has been well demonstrated, 45 and is a natural and well recognized progression to adulthood. Also, recent studies of androgen levels in elite athletes have suggested that female athletes with high testosterone levels, free or total, may have a significant competitive advantage over those with low testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…Before puberty there were small sex-related differences in strength and jumping ability [ 3 , 8 , 24 ]. In a study on USA swimming, it was noted that girls are faster than boys prior to puberty [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sex differences for Masters were smaller in running and long jump [11], or in swimming [22,23]. Before puberty there were small sex-related differences in strength and jumping ability [3,8,24]. In a study on USA swimming, it was noted that girls are faster than boys prior to puberty [4].…”
Section: Sex-related Performance Differs By Age and Body Massmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomised-control trials, non-randomised studies of interventions, and other observational studies which included males diagnosed with Hodgkin's lymphoma between the ages 13 and 51 who received anticancer treatment were included in this review. This age range was estimated to be when males are most fertile, between puberty onset and elderly decline in fertility [15][16][17]. Only studies using ABVD (Adriamycin® (doxorubicin), bleomycin, vinblastine, dacarbazine) or BEACOPP (bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, prednisolone) regimens were included as these regimens are the most common and effective treatments for HL [18,19].…”
Section: Study Eligibility Criteriamentioning
confidence: 99%